Classification criteria of forms for foreign direct investment - Nehrych, Olga (Skhid, 2013)
The main forms of foreign direct investment realization are described and analyzed in the article. The fundamental classification criteria of forms are: forms, based on contracts; with the aim of enterprise expansion; based on forms of participation and others.